The political economy of mercantilism - Magnusson, Lars, 1952-, author.
1 online resource (xi, 230 pages)
Keywords: "Since the days of Adam Smith, Mercantilism has been a hotly debated issue. Condemned at the end of the 18th century as a "false" system of economic thinking and political practice, it has returned paradoxically to the forefront in regard to issues such as the creation of economic growth in developing countries. This concept is often used in order to depict economic thinking and economic policy in early modern Europe; its meaning and content has been highly debated for over two hundred years. Following on from his 1994 volume Mercantilism - The Shaping of an Economic Language, this new book from Lars Magnusson presents a more synthetic interpretation of Mercantilism not only as a theoretical system, but also as a system of political economy. This book incorporates samples of material from the 1994 publication alongside new material, ordered in a new set of chapters and up-date discussions on mercantilism up to the present day. Tracing the development of a particular political economy of Mercantilism in a period of nascent state making in Western and Continental Europe from the 16th to the 18th century, the book describes how European rulers regarded foreign trade and industrialisation as a means to achieve power and influence amidst international competition over trades and markets. Returning to debates concerning whether Mercantilism was a system of power or of wealth, Magnusson argues that it is in fact was both, and that contemporaries almost without exception saw these goals as interconnected. He also emphasises that Mercantilism was an all-European issue in a time of trade wars and the struggle for international power and recognition. In examining these issues, this book offers an unrivalled modern synthesis of Mercantilist ideas and practices"--